“A Double-Edged Sword”: a case report on liver injury side-effect of Anti-Tuberculosis drug on liver Tuberculosis patient - Azlina Ibrahim; Alvin Oliver Payus (Universiti Malaysia Sabah, 2020)
Hepatic involvement in extra-pulmonary tuberculosis (TB) is rare, even in the endemic area. It has a high mortality rate as it can easily be misdiagnosed due to its rarity and non-specific presentations, and the treatment can be challenging for its hepatotoxic side-effect. A 55-year old man who was newly diagnosed with AIDS and pulmonary TB which complicated with anti-TB-induced transaminitis, presented with a few weeks history of fever and persistent diarrhoea. It was initially treated as microsporidia infection but the symptoms persisted despite given antiparasitic agent for more than a week. He was subjected to computed tomography (CT) scan of the abdomen and noted multiple hypoechoic lesion at multiple segments of the liver, which later confirmed to be liver TB by liver biopsy. As he could not tolerate Akurit-4 (Rifampicin 150 mg, Isoniazid 75 mg, Pyrazinamide 400 mg and Ethambutol 275 mg), the second-line treatment was given instead. He is currently well on regular clinic appointment. The objective of this case report is to share the rare occurrence of hepatic TB and the difficulty to treat it as the hepatotoxic effect of anti-TB medications complicate the liver damage due to the infection.